Persepsi Guru Terhadap Pendekatan Ilmiah di Sekolah Dasar - Hastuti , Retno Dwi (Nur Science Institute, 2023)
Background: The research aims to: 1) to describe teacher perception of scientific approaches in the implementation of 2013 curriculum learning in Mranggen State Elementary School 02; 2) to describe the implementation of scientific approaches in learning Curriculum 2013 in Mranggen Elementary School 02; 3) to describe barriers in the implementation of scientific approaches to the 2013 curriculum learning in Mranggen Elementary School 02; and 4) to describe the solution in the implementation of scientific approaches to learning Curriculum 2013 in Mranggen Elementary School 02. Method: This research is a qualitative descriptive study because researchers want to describe an event according to a real state and present data in the form of words. Result: The results of this study show that: 1) The perception of teachers feels burdened in time curriculum changes and authentic assessment techniques; 2) There is a difference in the ability of learners in the implementation of scientific learning in the 2013 curriculum; 3) Barriers that prominent the delay in channeling of handbooks and at least allocated funds; and 4) Provide training solutions to educators concerned with Curriculum 2013 in particular scientific approaches. Implication: Future research should focus on practical interventions to support teachers in addressing challenges related to the scientific approach, particularly with diverse student backgrounds. This study underscores the importance of teachers' perceptions and preparedness for the successful implementation of the 2013 Curriculum, offering valuable insights for policymakers and educational institutions to develop strategies that promote effective and meaningful learning in elementary schools. Novelty: This study provides a new contribution by specifically illustrating teachers' perceptions at SD Negeri Mranggen 02 regarding the implementation of the scientific approach in the 2013 Curriculum. It highlights practical challenges such as teachers' lack of preparedness, diverse student characteristics, and limited time and resources, while also presenting practical solutions from the school that can serve as a model for others..